HUBUNGAN TINGKATAN MASLAHAH DALAM MAQASHID AL-SYARI’AH (MASLAHAH AL-DHARURIYAT, AL-HAJIYAT, AL-TAHSINIYAT) DENGAN AL-AHKAM AL-KHAMSAH - Yosi Aryanti (El-Rusyd, 2017)
Muslim jurists have established a system of Islamic law and establish methods for the discovery of the law giving rise to the methods in istinbat using ushuliyah rules and norms of Islamic law fiqhiyah means of discovery. This means that both of these methods has provided space in tapping the text (nass al-Quran and as-Sunnah) to meet the legal needs of humanity, so that in its development, has led to studies critical that called for Islamic law can be brought benefit for humans and is considered important to be formulated based on essential values called "maqasid al-Shari'ah In an effort to develop Islamic legal thought, especially in providing an understanding and clarity on various issues of contemporary law, Mujtahids need to know the purpose pensyari'atan Islamic law in order to know for sure whether a legal provision is applicable to a particular case or because of changes in structure social, the law can no longer be maintained. Thus, knowledge of the maqasid al-shari'ah be the key to the success of mujtahid in ijtihad. The study of the levels of maslahah in maqashid Shari'ah (maslahah al-dharuriyat, al-hajiyat, al-tahsiniyat) has an integrated system that makes the arguments of Shari'a was in a braid intact, inseparable, and each other mutual support, as well as the proposition that one serves as an explanation for the arguments of others. To clarify the level of maqashid Shari'ah based classification dharuriyat, hajiyat and tahsiniyat, then relation to one another can be represented in al-Ahkam al-khamsah.